2021
DOI: 10.1021/acsabm.1c00473
|View full text |Cite
|
Sign up to set email alerts
|

Facile Multistep Synthesis of ZnO-Coated β-NaYF4:Yb/Tm Upconversion Nanoparticles as an Antimicrobial Photodynamic Therapy for Persistent Staphylococcus aureus Small Colony Variants

Abstract: Antibacterial treatment strategies using functional nanomaterials, such as photodynamic therapy, are urgently required to combat persistent Staphylococcus aureus small colony variant (SCV) bacteria. Using a stepwise approach involving thermolysis to form β-NaYF 4 :Yb/Tm upconversion nanoparticles (UCNPs) and surface ligand exchange with cetyltrimethylammonium bromide (CTAB), followed by zeolite imidazolate framework-8 (ZIF-8) coating and conversion to zinc oxide (ZnO), β-NaYF 4 :Yb/Tm@ ZnO nanoparticles were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…For example, polyacrylic acid (PAA) replaces OA ligands, [88][89][90] and PEG 600 diacid (HOOC-PEG-COOH) replaces OM or OA ligands. 91,92 In addition, it has been shown that polyvinylpyrolidone (PVP), 77,93 3-mercaptopropionic acid (3MA), 94 adipic acid (HDA) 95 and cetyltrimethylammonium bromide (CTAB) 96 can be used for ligand exchange modification experiments. Ligand oxidation achieves functional modification by oxidizing ligands on the surface of nanoparticles.…”
Section: Synthetization Methods Of Rare Earth-doped Nanocrystalsmentioning
confidence: 99%
“…For example, polyacrylic acid (PAA) replaces OA ligands, [88][89][90] and PEG 600 diacid (HOOC-PEG-COOH) replaces OM or OA ligands. 91,92 In addition, it has been shown that polyvinylpyrolidone (PVP), 77,93 3-mercaptopropionic acid (3MA), 94 adipic acid (HDA) 95 and cetyltrimethylammonium bromide (CTAB) 96 can be used for ligand exchange modification experiments. Ligand oxidation achieves functional modification by oxidizing ligands on the surface of nanoparticles.…”
Section: Synthetization Methods Of Rare Earth-doped Nanocrystalsmentioning
confidence: 99%
“…Hence, using UCNPs combined with NIR, the undesirable aspects of UV- and visible light-activated material can be accordingly addressed. As an example, Figure 3 illustrates the APDT mechanism of NaYF 4 : Yb 3+ /Er 3+ @ZnO ( Karami et al, 2021 ).…”
Section: Upconversion Luminescence Mechanismsmentioning
confidence: 99%
“… The dopant Yb 3+ and Tm 3+ ions convert 980 nm of NIR light into UV light. The ZnO in the outer layer of the core-shell structure absorbs UV light to produce ROS and achieve the antibacterial effect ( Karami et al, 2021 ). …”
Section: Upconversion Luminescence Mechanismsmentioning
confidence: 99%
“…While some studies intentionally generate UV light from UCNPs to directly influence or kill cells, most imaging applications do not consider the emissions in this range. This raises questions as to whether some UCNPs have significant energetic UV emissions that are not being detected, commonly due to most spectral systems having difficulty readily characterizing UV emissions.…”
Section: Introductionmentioning
confidence: 99%